Analisis Implementasi Pengembangan Projek Penguatan Profil Pelajar Pancasila Smp Di Jakarta Barat Pada Kurikulum Merdeka Mandiri Berbagi - agustina, hendra; Hindriana, Anna Fitri; Nur, sofyan H. (Peneliti.net, 2023)
At this time, the challenges of the rapid flow of globalization and technology are increasingly challenging. Education has an important role in answering and preparing the current and next generations. Through ongoing curriculum development, this is one answer to meeting the required competencies. Indonesia, through the Ministry of Education, Culture, Research and Technology of the Republic of Indonesia, always strives to create innovations in improving the quality of education in Indonesia in order to create a generation of people who are tough and able to face the challenges of the times, especially in curriculum changes. The independent curriculum or what was previously known as the prototype curriculum has already been implemented. inaugurated by the Ministry of Education, Culture, Research and Technology (Kemendikbudristek) starting from the 2022/2023 academic year (Kemendikbud, 2022). The way for the Merdeka Curriculum to run well is first by aligning perceptions to create one vision. Then the curriculum is implemented slowly, after that it is evaluated if a problem occurs. The aim of this research is to determine the implementation of P5 activities as a project to strengthen the Pancasila Student Profile in schools and the impact of its implementation on students. This research was conducted at a public junior high school in Jakarta which implemented P5 in the independent curriculum. The sample in this study consisted of 3 schools. The method used is a qualitative method with a descriptive approach. The data collection techniques used were interviews by researchers with sources, namely science teachers who taught class VII who had implemented the independent curriculum, P5 facilitators, teacher questionnaires for science teachers who taught class VII, and student questionnaires for class VII students. The document analysis used is the P5 activity module. The results of this research are that the implementation of P5 (Strengthening the Pancasila Student Profile Project) in the independent and sharing curriculum has prioritized project-based learning in order to realize the Pancasila student profile. In developing the P5 module (Strengthening Pancasila Student Profile Project) in developing the Pancasila student profile, some schools are already familiar with Project Based Learning, the application of problems that are not yet contextual and learning that is not in accordance with student needs so that learning is not yet differentiated. The response to the implementation of P5 (Strengthening the Pancasila Student Profile Project) in the development of the Pancasila student profile was that 36% of students responded